ANALYSIS OF THE RELATIONSHIP BETWEEN GASTROESOPHAGEAL REFLUX DISEASE (GERD) AND PATIENTS’ SMOKING PATTERNS AND COFFEE CONSUMPTION - Gangga Mahatma; Vina Tri Septiana; Irwan Triansyah; Dessy Abdullah; Ade Teti Vani (Community Development Journal : Jurnal Pengabdian Masyarakat, 2023)
The aim of this study was to investigate the association between coffee drinking, smoking, and the prevalence of gastroesophageal reflux disease (GERD) in college students. This study is an observational analytic cross-sectional study that employs a quantitative methodology. 200 participants were chosen at random from a basic random sample in order to conduct this study. In this research, the findings of the chi-square examination conducted to determine the correlation between coffee intake and the occurrence of GERD revealed a noteworthy association between the two variables. Similarly, the results of the chi-square test conducted to establish the link between smoking practices and the incidence of GERD demonstrated a significant association between the two. Consequently, it can be inferred that there is a significant correlation between coffee consumption, smoking habits, and the incidence of GERD in college students.